Quality circle implementation and customers' perceived satisfaction at an Air Force hospital - Bautista, Evelyn B. (2003)
This study sought to determine if there are any changes in the internal and external customers' perceived satisfaction brought about by the implementation of Quality Circle at AFGH. Specifically, it determined if there were significant differences in the customers' perceived satisfaction in relation to the nurses' competence (technical, interpersonal and teaching skills). A quasi-experimental non-equivalent pre-test - post-test design was used. Thirty (30) internal customers composed of military and civilian doctors, military nurse supervisors, head nurses and thirty five (35) external customers from the Military ward and Surgical ward of AFGH were invited as participants. Questionnaires were distributed before and after the Quality Circle implementation to assess the Quality Circle (QC) nurses. The twenty-five (25) QC nurses had self-assessment questionnaires on how effective the weekly QC meetings were. The data was subjected to analysis using descriptive statistics (measures of central tendency and dispersion) and inferential statistics (paired t-tests) and the results are as follows: (1) There was a significant difference in both the internal and external customers' perceived satisfaction in relation to nurses' competence as to technical, interpersonal, and teaching skills before and after QC implementation. (2) The scores of perceived satisfaction of both internal and external customers were highest in the category of technical skills followed by teaching and interpersonal skills respectively. (3) The internal and external customers highly rated nurses' competence after the Quality Circle implementation. The technical and teaching skills of the QC nurses were enhanced and their interpersonal skills were markedly improved. (4) Quality Circle nurse participants perceived their performance / involvement in the Quality Circle meetings as very effective and there was an improvement in every meeting. Findings of the study will encourage top management leadership to commit themselves to quality services and engage furthermore in quality improvement activities such as this. It is recommended that a replication of this study be done in similar military hospitals.
Vita.
Thesis (MA Nursing) -- University of the Philippines, Manila.
Keywords: Quality circles